Formative assessment in the training of technical students - Issalieva, A.A.; Iskalieva, A.T. (KSU publ., 2020)
The article deals with the issues of formative assessment. Formative assessment focuses on improving learning outcomes and teaching. It provides feedback to guide learning and learning for the learner. The significance of this article consists in that theoretical positions, conclusions developed during research, can find the use in the process of preparation of futurespecialists of technical profile; worked out and approved methodology of diagnostics and stage-by stage formative evaluation of students of technical specialities can be used in teaching of subject «Russian» in technical institution of higher learning; recommendations and provisions are given on to creation of the system of methodical bases of formative evaluation of students in accordance with by the qualified model of graduating student technical technical institution of higher learning.
Keywords: assessment; technology; learning; research; formative assessment; learning achievement; methods